Hak Ex Offcio Hakim: Studi Kasus Perceraian di Pengadilan Agama Sidoarjo No. 3513 Th. 2015 - Ahmad Fanani (Universitas Darussalam Gontor, 2017)
There are still many husbands who decide to divorce without giving the rights belong to their wives and the children they have. Whereas, the divorce does not mean removing the obligations of a husband toward his child and his ex-wife. In the process of examining cases in giving a verdict, a Judge would not give more than required judgment in the lawsuit of the petition. On the other hand, the Judge has an ex offcio right, so that the Judge may oblige the husband to fulfll the rights of divorced wives even though they are not in the the lawsuit of the petition. In Islamic law, the obligation is also determined. This study concludes that the judge in the divorce judgment in Sidoarjo religious court uses his ex offcio to decide the rights of the wife during ‘iddah’ and ‘mut’ah’ that is not requested by by her following these considerations: to give lessons to any husbands to avoid divorce; to guarantee a justice for any wives who got divorced. The application of ex offcio right of the judge in the divorce case in Sidoarjo religious court is in accordance with Islamic law in the process of charging the cost of living ‘iddah and mut’ah based on principles of justice and maṣlaḥah mursalah, thus realizing the beneft to the former wife after being divorced